Pressing forward : increasing and expanding rigor and relevance in America's high schools - Smerdon, Becky; Borman, Kathryn M. (Emerald Publishing Limited : Information Age Publishing, 2012)
Pressing Forward: Increasing and Expanding Rigor and Relevance in America's High Schools is organized to place secondary education, specifically the goals of preparing young adults to be college and career ready, in contemporary perspective, emphasizing the changing global economy and trends in policy and practice. High school students must be equipped with tools they need during and beyond high school for mapping their futures in a global and flat world that demands workers prepared to take up 21st century careers. Following Thomas Freidman and other writers on the topic, this book takes as its core premise that the world has been irrevocably altered by technology and that technology takes a prominent role in shaping post-secondary education and career opportunities. The challenges facing education and educators in a flattened world can best be addressed by creating opportunities for students who are ready for a world in which they are expected to pursue learning throughout their lifetimes, understand and use technology, engage in active civic lives, function well in ethnically diverse workplace settings, and be willing to take risks. Most of all, however, these individuals must be very well prepared during high school by taking advanced level mathematics, science and other challenging coursework, while at the same time actively engaging in collaborative, creative endeavors that prepare them to continuously reinvent themselves to stay ahead of automation and outsourcing.The book will be a unique and useful contribution to the education reform and policy literature as it examines secondary education at an historical moment--the convergence of significant education spending and focus on high school reform. Developed from diverse authors' research programs on secondary education, the chapters in this volume highlight both changing and steadfast features of high schools, questioning if attempts to foster change--whether tinkering around the edges or inventing a new way--adequatly adress shortcomings in equity and excellence found in American high schools.
Keywords: Education, Secondary -- United States.; School improvement programs -- United States.; Education -- Schools -- Levels -- Secondary.; Secondary schools.; elektronické knihy; electronic books